Uji Fisik Sediaan Serum Wajah Ekstrak Akar Alang-alang (Imperata cylindrica L.) - Febriani, Alik Kandhita; Rejeki, Desi Sri (Jurnal Riset Farmasi, 2025)
Abstract. Skin problems have driven the development of safe and effective natural-based skincare products. Cogon grass roots (Imperata cylindrica L.) contain bioactive compounds such as flavonoids, saponins, and tannins, which exhibit antioxidant and antibacterial activities and show potential as cosmetic active ingredients. This study aimed to formulate and evaluate the physical characteristics of a facial serum containing cogon grass root extract. The extraction process was carried out using ethanol as the solvent, and the extract was formulated into three serum formulations with varying extract concentrations. Physical evaluations included organoleptic properties, homogeneity, pH, spreadability, and freeze–thaw stability tests. The results indicated that all formulations exhibited good organoleptic characteristics and satisfactory homogeneity. The pH of all serum formulations was 6, which falls within the safe range for facial skin. Spreadability test results for the three formulations were 5.4 cm, 5.2 cm, and 5.0 cm, respectively, meeting the standard requirements for serum preparations. Freeze–thaw stability testing over six cycles showed no significant changes in color, odor, or consistency. These findings support the potential use of cogon grass root extract as a cosmetic active ingredient and provide a scientific basis for the development of stable and safe facial serum products derived from local natural resources with potential application in the cosmetic industry. Abstrak. Permasalahan kulit mendorong pengembangan produk perawatan kulit berbahan alami yang aman dan efektif. Akar alang-alang (Imperata cylindrica L.) mengandung senyawa bioaktif berupa flavonoid, saponin, dan tanin yang memiliki aktivitas antioksidan dan antibakteri sehingga berpotensi digunakan sebagai bahan aktif kosmetik. Penelitian ini bertujuan untuk memformulasi serta mengevaluasi karakteristik fisik serum wajah berbasis ekstrak akar alang-alang. Ekstraksi menggunakan pelarut etanol, kemudian ekstrak diformulasikan ke dalam tiga formula serum dengan variasi konsentrasi. Evaluasi fisik meliputi uji organoleptik, homogenitas, pH, daya sebar, serta uji stabilitas freeze–thaw. Hasil pengujian menunjukkan seluruh formula memiliki karakteristik organoleptik yang baik dan homogen. Nilai pH seluruh sediaan berada pada angka 6, sesuai dengan rentang pH aman untuk kulit wajah. Uji daya sebar menunjukkan nilai berturut-turut 5,4 cm; 5,2 cm; dan 5,0 cm, yang memenuhi persyaratan daya sebar serum. Uji stabilitas freeze–thaw selama enam siklus menunjukkan tidak adanya perubahan warna, bau, maupun konsistensi. Penelitian ini memberikan kontribusi ilmiah dalam pengembangan pemanfaatan bahan alam lokal sebagai bahan aktif kosmetik, serta menjadi dasar formulasi produk serum wajah berbasis akar alang-alang yang stabil, aman, dan berpotensi dikembangkan lebih lanjut pada skala industri kosmetik